EVALUASI PEMIDANAAN TERHADAP PENYALAH GUNA NARKOTIKA YANG MEMPENGARUHI OVER KAPASITAS RUTAN KELAS I LABUHAN DELI - Sinambela, Lasma; Ismaidar, Ismaidar; Ramadani, Suci (Penerbit Lafadz Jaya, 2025)
Overcapacity of correctional institutions in Indonesia is still a serious problem, one of the main causes is the high criminal prosecution rate against drug abusers. Repressive approach through prison sentences proved unable to resolve the root of addiction, and it worsens the condition of the correctional institution, including Class I Rutan Deli. The study aims to evaluate the effectiveness and impact of criminal offences on drug abusers, analyze applicable legal policies, and assess the contribution of such policies to the overcapacity of the termite. This Research Method uses empirical juridics with a qualitative approach, where data is obtained through library studies, legal documentation, as well as direct interviews with routine officers, law enforcement officials, and inmates. The results of the study showed that criminalizing narcotic abusers was ineffective in addressing addiction and actually increased the risk of residivism. Most of the drug inmates in the routine are users, not dealers, who should get rehabilitation, not prison. Applicable legal policies, particularly Law No. 35 of 2009 on Narcotics, actually provide space for rehabilitative approaches. However, its implementation on the ground is still minimal due to the dominance of the punishment approach. Law enforcement is more oriented to prison criminal criminal than to provide rehabilitation services. As a result, the correctional system becomes overwhelmed and the recovery process for drug abusers does not run optimally. Evaluation of conditions in Class I Rutan Labuhan Deli showed that the penalty directly impacted the surge in the number of residents of the routine and aggravated overcapacity. Therefore, the study recommends reforming legal policy by putting forward rehabilitative approaches and restorative justice. Interagency synergies, rehabilitation agencies, and paradigm changes in the criminal justice system in order to handle drug abusers to be more effective, humane, and sustainable.